Effect of Inlet Air Heating on the Performance of Gas-Steam Combined Cycle Power Plant Unit - Tao ZHANG; Zhitan LIU; Xue GAN; Zhongguang FU; Zhiyuan YAN; Hongfei ZHU; Zhenbo QIU (Zhongguo dianli)
Taking a 200 MW-class gas-steam combined cycle power plant unit(GSCC) as the research object, the exhaust heat in the tail flue of the HRSG was utilized to heat the feed water, which was directed afterwards into the gas-water heat exchanger to raise the inlet air temperature of the compressor. The parameter changes before and after the operation of the inlet air heating system were simulated by Aspen Plus and furthermore, the influence of inlet air heating on the performance of the GSCC at partial load was analyzed. Results show that when the inlet temperature of the compressor rise from 12.5 °C to 35 °C under the load of 50%, 75% and 87% of GSCC, the load rate of the gas turbine increases by 0.08, 0.12 and 0.15 respectively, while the fuel flow rate drops down by 0.11 kg/s, 0.13 kg/s and 0.10 kg/s respectively, and the combined cycle efficiency goes up by 1.04%, 1.03%, and 0.73% respectively. Under 95% load, the load rate of the gas turbine increases from 0.95 to the maximum 1.00, and the combined cycle efficiency increases first before taking a dip. Under 100% load, the load rate of the gas turbine remains unchanged at 1.00, while the heat efficiency of GSCC decreases continually.